Pulmonary artery catheter epidemiology of risk in pre–heart-transplant recipients. (30th April 2019) - Yetmar, Zachary A; Lahr, Brian; O'Horo, John; Behfar, Atta; Sampathkumar, Priya; Beam, Elena
Abstract: Objective: Central-line–associated bloodstream infections (CLABSIs) are a known complication of central venous access. Pulmonary artery catheters (PAC) are frequently used in pre–heart-transplant patients, but the rate of CLABSI in this population is unknown. We sought to estimate the rate of CLABSI and identify factors associated with development of infection in patients actively listed for heart transplantation with a PAC. Design: Retrospective cohort study. Setting: This study was conducted in 3 intensive care units at an academic tertiary-care center in Minnesota. Patients: 61 pre–heart-transplant patients in an intensive care unit with a PAC in place from January 2013 to December 2016, totaling 219 PACs. Methods: At-risk patients, pertinent risk factors, and demographic data were obtained using Mayo Clinic's Unified Data Platform. CLABSIs were identified through internal infection prevention and control data. Characteristics of PAC use and infection rate were collected and analyzed using Kaplan-Meier estimates and time-dependent Cox models. Results: Among pre–heart-transplant patients with a PAC, there were 14 CLABSIs, for an infection rate of 5.46 of 1, 000 PAC days (95% confidence interval [CI], 2.98–9.15). The most common causative organism was coagulase-negative Staphylococcus (79%). In unadjusted analyses, CLABSI was associated with shorter time to transplant (hazard ratio [HR], 2.49; P = .027), but not mortality (HR, 1.79; P = .355). Conclusions: The rate of CLABSI with PAC is high. Prolonged PAC use in the pre–heart-transplant population should be revisited.